Le bagne portuaire de Rochefort (1766-1852) : un patrimoine disparu - Philippe Duprat (In Situ)
The penal prison of Rochefort was a confined space with different sites spread in the arsenal and in town. It is now a lost and forgotten heritage. The memory of the site itself and of the institution has sunk into complete oblivion, unlike the most emblematic monument of Rochefort, the Corderie Royale (rope manufacture) which was in the same state of extreme dilapidation after being blown up in 1944.This article aims at focusing on the history of Rochefort harbour prison which had up to 25,000 inmates over a period of 86 years (1766-1852). More than 50% died in detention.The original buildings which had been hastily put up could not receive more than 600 men. During the American War of Independence more buildings had to be put up to increase the prison capacity. They were gradually extended and fitted out as the number of inmates grew until the prison maximum capacity was reached.In the 19th century the rapid growth of steam engines and trains and a lack of qualified labour among the detainees led the prison to close down in 1852. The old prison was converted into industrial premises giving the arsenal a new start. The industrial vocation of the place still continues today after the interludes of wartime German occupation and the post war US NATO basis. Air industry buildings now stand on the historical site of the prison transformed into a myth by the French novelist Balzac.